Preparation method of zinc-loaded attapulgite with high bioavailability

By activating, ultrasonic dispersing, acidifying and zinc-carrying coating, high-bioavailability zinc-carrying concave rock stones are prepared, solving the environmental pollution and zinc excretion problems caused by high dose use of zinc oxide, and realizing the The precise delivery and efficient utilization of zinc are achieved.

CN119490192APending Publication Date: 2025-02-21JIANGSU SINITIC BIOLOGICAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411620643.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, high doses of zinc oxide are used in livestock industry to prevent diarrhea from piglets, but its excessive use results in increased environmental pollution and zinc excretion, and there are insufficient alternatives.

Method used

Two-stage heating is used to activate the concave and concave rock stone, and its specific surface area and adsorption performance are improved by ultrasonic dispersion and acidification treatment. The modified concave and concave rock stone is then reacted with zinc sulfate to carry zinc, and finally carboxylated chitosan and tannin. Covering the high bioavailability zinc-loaded concave rock stone.

Benefits of technology

It significantly reduces the amount of zinc used and environmental pollution, improves the bioavailability of zinc, realizes the precise delivery of zinc ions and reduces the excretion of unabsorbed zinc ions, and provides a saving and efficient zinc supplementation strategy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a preparation method of zinc-loaded attapulgite with high bioavailability, and belongs to the technical field of functional composite materials. The attapulgite is modified through activation, ultrasonic dispersion and acidizing treatment, the specific surface area of the attapulgite is increased, the cation exchange capacity is increased, the problem that zinc ions are loaded in the attapulgite less is further solved by optimizing the zinc loading condition, and finally, accurate putting of the zinc ions is achieved through coating operation, so that the content of the zinc ions in the attapulgite is increased. The bioavailability of zinc ions is improved, the discharge of unabsorbed zinc ions is remarkably reduced, the burden on the ecological environment is reduced, and the requirement of sustainable development is met. Compared with zinc oxide, the zinc-loaded attapulgite with high bioavailability prepared by the method can realize similar or better growth and health performance under the condition of using lower zinc dosage, provides an economical and efficient zinc supplement strategy, has obvious advantages when the zinc dosage needs to be optimized, and achieves the purposes of reducing the use amount and replacing zinc oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and relates to a method for preparing a modified attapulgite zinc-loaded material for animal husbandry, and in particular to a method for preparing zinc-loaded attapulgite with high bioavailability. Background Art

[0002] With the development of modern pig farming, diarrhea in piglets has always been an important factor affecting their health and growth. Traditionally, in order to solve this problem, feeding high doses of zinc oxide (≥1500ppm) has been widely used in practice. Zinc oxide has certain effects in reducing diarrhea in piglets, inhibiting the proliferation of bacteria and viruses, and promoting growth. In the process of using zinc oxide, high doses of zinc will significantly increase the excretion of zinc by animals. During feeding, zinc oxide first reacts with gastric acid to form zinc ions, which easily combine with plant-derived feed in the pig diet to form insoluble complexes. A large amount of unused zinc ions are excreted from the body with feces; data show that when 15-18Kg pigs are fed diets containing 23mg / Kg and 123mg / Kg of zinc, respectively, the daily zinc excretion of pigs fed with low-zinc diets is 16mg, while the daily zinc excretion of pigs fed with high-zinc diets is 61mg, which is 3.6 times higher. The use of low doses of zinc oxide does not achieve the expected effect.

[0003] A large amount of unabsorbed zinc ions enter the ecological environment directly with excrement, significantly increasing the zinc burden in the soil and causing long-term environmental pollution. For example, the EU has banned the use of pharmacological doses of zinc oxide in animal feed since 2003, and it can only be used as a veterinary prescription. Canada, Japan and other countries have successively set limits on zinc in feed. my country further limited zinc in feed in 2005, 2009 and 2017, respectively. The latest requirement is that the maximum limit of zinc in piglet (≤25kg) compound feed is 110mg / kg, and zinc oxide or basic zinc oxide is allowed to be used up to 1600mg / kg in the first two weeks after weaning. However, even so, the problem of reducing zinc oxide substitution has not been completely solved. Antibiotics are often used as the main means of treating diarrhea, but the problems of antibiotic residues and drug resistance they bring are also becoming increasingly prominent, causing food safety concerns.

[0004] Therefore, how to effectively reduce the use of zinc oxide in feed and seek safe and effective alternatives has become the focus of current research in the livestock industry. Summary of the invention

[0005] The purpose of the present invention is to solve the above problems in the prior art and to provide a method for preparing zinc-loaded attapulgite with high bioavailability.

[0006] The object of the present invention can be achieved by the following technical scheme: A preparation method of zinc-loaded attapulgite with high bioavailability comprises the following steps: S1 modification treatment: activating the attapulgite by a two-stage heating method to obtain activated attapulgite; adding the activated attapulgite to ethanol, performing ultrasonic dispersion at 45-50°C, filtering and washing after the ultrasonic dispersion to obtain fine attapulgite; acidifying the fine attapulgite, filtering and washing to obtain modified attapulgite;

[0007] The parameters of attapulgite are as follows: particle size is 20-30nm, the length of attapulgite is 1-1.5um; silicon dioxide content is 51.264%-52.139%; magnesium oxide content is 9.765%-9.812%; aluminum oxide content is 12.104%-12.367%; calcium oxide content is 10.375%-10.963%; iron oxide content is 7.379%-7.469%; potassium oxide is 1.864%-1.876%; sodium oxide is 0.689%-0.715%, and the loss on ignition is 6.572-6.749%;

[0008] Particle size setting (20-30nm): The particle size of attapulgite has a direct impact on its surface area and chemical activity. Selecting a smaller particle size (20-30nm) can increase the total surface area and provide more active sites, because more surface area can increase the contact opportunities with the treatment reagents, thereby improving efficiency and reaction integrity.

[0009] Length of attapulgite (1-1.5 μm): This length range provides sufficient structural support, maintaining the unique properties of nanomaterials while avoiding the difficulty of handling due to excessive length. Controlling the length within this range is conducive to maintaining good mechanical strength and stability during handling.

[0010] The purposes of the modification treatment are as follows: 1. to dredge the pores, increase the specific surface area, and improve the adsorption performance of attapulgite; 2. to increase the cation exchange capacity, so as to promote more zinc ions and attapulgite to undergo ion exchange reaction in step S2;

[0011] Effects of heating activation: Improve physical properties: Heating can change the crystal structure of attapulgite, increase its specific surface area and porosity. Enhance mechanical stability: Through heating treatment, the structure of attapulgite will become more stable, which is beneficial for the material after multiple stirring, dispersion and reaction processes. Improving mechanical strength helps to maintain the integrity of the material in subsequent processing steps.

[0012] Although the activation process has removed some of the impurities and organic matter on the surface by heating, there are still some impurities that are not easy to remove. Then ultrasonic dispersion is carried out. The effects of ultrasonic dispersion are as follows: 1. Changes in particle morphology and surface roughness: The strong vibration of ultrasound can change the surface morphology of particles and increase surface roughness. Rough surfaces have more tiny bumps and irregular structures than smooth surfaces; 2. Removal of impurities: Ultrasonic waves use the cavitation effect to effectively break the binding force between impurities and activated attapulgite, making the particle surface purer, and the sound wave vibration effect helps to peel off impurities that are difficult to remove. Reasons for choosing ethanol: 1. Reduce viscosity: Compared with water, ethanol can reduce the viscosity of the dispersion system, making the particles easier to move and disperse in the solution: 2. Selective dissolution: Ethanol has a certain polarity. By placing the activated attapulgite in ethanol, these impurities can be dissolved and removed from the particle surface. 3. Easy to remove: During the cleaning process, ethanol can be easily removed by washing with clean water. Choose a temperature of 45-50℃: Optimize the dissolution and diffusion rate: At this temperature, the kinetic energy of ethanol molecules increases, which helps to increase the dissolution and diffusion rate, thereby accelerating the dispersion process. Controlling the volatilization rate: Ethanol is easy to volatilize at high temperatures. Selecting the temperature range of 45-50°C can improve the dispersion efficiency while avoiding too fast volatilization that affects the dispersion effect and operation safety. Protecting material properties: This temperature range is also mild enough to prevent the performance change or decomposition of attapulgite due to overheating. Therefore, ultrasonic dispersion in and out of ethanol can remove impurities and improve the purity of the attapulgite surface on the one hand, and increase the total specific surface area of ​​the material on the other hand.

[0013] The purpose of acidification after ultrasonic dispersion is as follows: during the acidification process, at a certain concentration of hydrogen ion content, hydrogen ions can replace metal ions such as magnesium ions, aluminum ions and iron ions contained in attapulgite clay, and the replacement of these metal ions improves the cation exchangeability of attapulgite; the acidic solution can effectively dissolve some chemically bound impurities, especially those substances that are bound to the surface of attapulgite by ionic bonds or chemical bonds. The acid molecules react with the impurities to destroy their binding force with attapulgite, thereby removing these impurities, improving the surface purity and pore dredging of the attapulgite, thereby increasing the specific surface area and improving the adsorption capacity;

[0014] S2 zinc loading: adding modified attapulgite to deionized water, adding biosurfactant, stirring until uniform, obtaining an emulsified suspension, adding zinc sulfate solution to the emulsified suspension, obtaining a mixed suspension, subjecting the mixed suspension to ultrasonic stirring at a temperature of 60-65°C, and during the stirring process, regularly measuring the concentration of zinc sulfate in the mixed suspension to ensure that the concentration of zinc sulfate is not less than 0.1M; after the stirring is completed, filtering and washing are performed to obtain initial zinc-loaded attapulgite;

[0015] According to the weight ratio, the modified attapulgite:biosurfactant is 1:0.0025-0.003;

[0016] The biosurfactant is prepared from an invention patent with the publication number of CN117256728B which has been authorized by our company;

[0017] The purpose of ultrasonic stirring is to shorten the reaction time. In the zinc loading process, the uniform dispersion and adsorption of zinc ions are the key. Ultrasonic waves can help promote the rapid and uniform distribution of zinc sulfate in the emulsified suspension, while enhancing the adsorption capacity of attapulgite for zinc ions. Ultrasonic waves reduce the interfacial resistance on the particle surface through vibration and cavitation effects, making it easier for ions to pass through the liquid-solid interface, further increasing the exchange rate of ions.

[0018] During the ultrasonic stirring process, an ion exchange reaction occurs. Due to the high concentration of zinc ions, according to the LeChatelier principle, the system spontaneously moves in the direction of reducing the zinc ion concentration in the solution, prompting more zinc ions to replace hydrogen ions and other metal ions in attapulgite until a new equilibrium state is reached. Zinc ions carry a double positive charge, which makes them more attractive during the ion exchange process. Compared with single positively charged metal ions (such as potassium ions) or calcium ions with larger ionic radius, zinc ions have priority in the exchange position; because the ionic charge of Zn2+ is higher than that of hydrogen ions, and the ionic radius of zinc ions is suitable for embedding into the structural pores of attapulgite, this provides a good condition for replacement.

[0019] In the acidification treatment of step S1 and the replacement reaction of step S2, the key parameters for achieving the ion replacement reaction are concentration and temperature. In step S1, other metal ions can be replaced by high concentration hydrogen ions. In step S2, hydrogen ions and other ions that are not easily replaced by hydrogen ions can be replaced by high concentration zinc ions. Therefore, in order to ensure that the prepared zinc-loaded attapulgite can carry more zinc, strict requirements are imposed on the parameters of the attapulgite.

[0020] In an acidic environment such as gastric juice, the concentration of hydrogen ions is high. These hydrogen ions can gradually exchange with the zinc ions in the attapulgite. Since the release of zinc requires continuous exchange and penetration of hydrogen ions, as well as diffusion restrictions within the attapulgite structure, the release of zinc ions exhibits slow kinetic characteristics. In this way, the initial zinc-loaded attapulgite is obtained. Even if the coating operation is not thorough in the subsequent coating step, the release rate of zinc ions is very slow, which can effectively reduce premature release.

[0021] S3 coating: add carboxylated chitosan to deionized water at 40-60°C, stir until uniform, then add citric acid to adjust the pH value of the solution to 4-5; then add the initial zinc-loaded attapulgite, continue to stir until uniform, finally add tannic acid, stir at a temperature of 45-50°C, after stirring, let stand for a certain period of time, finally filter and dry to obtain zinc-loaded attapulgite with high bioavailability; in the filtration operation, use a semi-frame filtration device;

[0022] The parameters of carboxylated chitosan are as follows: molecular weight is 90000-110000 Dalton; degree of substitution is 0.85-0.95; purity of carboxylated chitosan is not less than 95%;

[0023] In terms of weight ratio, the weight ratio of carboxylated chitosan: initial zinc-loaded attapulgite: tannic acid is 2.2-2.4:100:1.08-1.1.

[0024] Carboxylated chitosan is an enteric coating material with good biocompatibility and biodegradability. During the preparation process, carboxylated chitosan can form a coating layer on the surface of attapulgite. Tannic acid is a natural polyphenol compound that can form a cross-linked structure with carboxylated chitosan to enhance its stability and durability. This protective layer can effectively isolate the direct contact between attapulgite and digestive enzymes (such as pepsin) in gastric juice, thereby reducing the digestion and degradation of attapulgite in gastric juice. When the coated attapulgite enters the intestine, the coating material is digested and absorbed in the intestinal environment, thereby achieving the purpose of accurately releasing zinc ions. Compared with zinc oxide, zinc ions are generated in gastric juice. Zinc ions easily combine with plant-derived feed in the pig diet to form insoluble complexes. Only a small amount of zinc ions enter the intestine, greatly reducing the amount of zinc used.

[0025] Other advantages of carboxylated chitosan: Promote intestinal health: Carboxylated chitosan has good biocompatibility and biodegradability, and can be used as a prebiotic to promote the growth of beneficial bacteria in the intestine, thereby improving the balance of intestinal microecology. Antibacterial effect: Carboxylated chitosan has certain antibacterial properties, which can inhibit the growth of pathogenic bacteria in the intestine, reduce the risk of intestinal infection, and enhance the immunity of animals.

[0026] Other benefits of tannic acid: Antioxidant effect: Tannic acid is a natural polyphenol compound with significant antioxidant properties. It can scavenge free radicals, protect intestinal cells from oxidative damage, and promote intestinal health. Anti-inflammatory effect: Tannic acid can inhibit inflammatory response, reduce intestinal inflammation, help relieve symptoms of intestinal discomfort and inflammatory diseases, and improve intestinal function. Enhance intestinal barrier function: Tannic acid can enhance the integrity of intestinal epithelial cells, improve intestinal barrier function, reduce the penetration of harmful substances and pathogens, and thus protect intestinal health.

[0027] The conditions for setting the pH value to 4-5 are considered as follows: 1. Under this pH condition, the zinc in the initial zinc-loaded attapulgite can remain stable; 2. The solubility of carboxylated chitosan is improved to ensure that the carboxylated chitosan is fully dissolved in the solution to form a uniform colloidal solution, which is convenient for subsequent coating operations.

[0028] Since biological materials are used in this step, they do not need to be washed and can be directly dried after filtering.

[0029] Preferably, in step S1, the specific steps of the activation operation are as follows: the attapulgite is heated at a temperature of 100-200°C for the first stage, and after the first stage heating is completed, the heating temperature is increased to 250-280°C for the second stage heating.

[0030] The activation treatment of attapulgite by two-stage heating is mainly to ensure that the structure and chemical properties of the material are gradually and effectively adjusted, while avoiding the negative effects caused by too fast heating. This gradual heating method has the following key purposes and advantages: 1. Gradual removal of moisture and impurities: During the first stage of heating (100-200℃), the main purpose is to remove the moisture physically adsorbed on the surface and pores of attapulgite. This temperature range is sufficient to evaporate the adsorbed water and part of the bound water, but it will not overheat and damage or change the microstructure of the material. If a higher temperature is used directly, it may cause rapid expansion or structural damage of the material, so gradual heating can effectively control this risk. 2. Heating in the second stage (250-280℃): 250-280 degrees can more effectively remove the structural moisture bound to the crystal and the adsorbed organic impurities, which can optimize its pore structure, provide a larger specific surface area and better adsorption performance. These substances may not be completely removed at lower temperatures; the temperature range of 250-280 degrees will not damage the crystal structure of the material when removing more stubborn organic substances and some chemical impurities in attapulgite. This temperature range is not enough to cause crystal phase changes or structural collapse, which is crucial to maintain the long-term stability and activity of the material.

[0031] Preferably, the parameters of the ultrasonic dispersion operation are as follows: ultrasonic frequency range: 30kHz to 50kHz; ultrasonic power range: 300W to 500W; ultrasonic time range: 15 minutes to 25 minutes; ultrasonic amplitude: 20-40um; ultrasonic gap: 1-3mm, ultrasonic device type: immersed ultrasonic generator; in terms of weight ratio, the weight ratio of acidified attapulgite to ethanol is 1:5.38-7.17.

[0032] Uniform dispersion: The main purpose of ultrasonic dispersion is to evenly disperse the active attapulgite in ethanol to avoid particle agglomeration. By selecting the appropriate ultrasonic frequency (30kHz to 50kHz), sufficient cavitation effect can be effectively generated to promote the dispersion of particles.

[0033] Controlling energy input: The ultrasonic power (300W to 500W) is set within this range to ensure that there is enough energy to break the interaction forces between particles while avoiding excessive power that causes particle destruction or excessive thermal effects.

[0034] Time optimization: The ultrasonic time (15 min to 25 min) was set to ensure that dispersion was completed within a reasonable time while avoiding heat accumulation and potential damage to particles caused by excessive ultrasonication.

[0035] Amplitude and gap adjustment: The selection of ultrasonic amplitude (20-40μm) and ultrasonic gap (1-3mm) is to optimize the propagation effect of ultrasonic waves and ensure that ultrasonic waves can be effectively transmitted to the liquid, thereby enhancing the dispersion effect while maintaining the stability of the equipment.

[0036] Ultrasonicator type: The immersion ultrasonic generator is selected because it can generate ultrasonic waves directly in the liquid, has good energy transfer efficiency, and is suitable for dispersion operations in liquids.

[0037] Setting of weight ratio: The weight ratio of activated attapulgite to ethanol (1:5.38-7.17) ensures that during the ultrasonic dispersion process, the ratio of solid to solvent is appropriate, which can ensure sufficient dispersion of particles without causing excessive solvent.

[0038] Preferably, in S1, the specific steps of the acidification treatment operation are as follows: after the fine concave-convex and deionized water are uniformly mixed, a hydrochloric acid solution is added to adjust the pH value to 3.0-3.3, and stirring is performed at a temperature of 60° C. for 2-2.5 hours.

[0039] Preferably, in step S2, the ultrasonic stirring operation parameters are as follows: ultrasonic frequency: 28-30kHz; ultrasonic power: 250-270W; amplitude: starting from 30um and gradually increasing to 50um; ultrasonic time: 60-70 minutes.

[0040] Ultrasonic stirring operation parameters: Ultrasonic frequency (28-30kHz): Increasing the frequency can enhance the energy transfer of ultrasound, further promote the dispersion and modification reaction of particles, and improve the reaction efficiency. Ultrasonic power (250-270W): Providing higher energy within this range helps to accelerate chemical reactions and enhance the surface modification effect of particles. Amplitude (gradually increasing from 30μm to 50μm): Using a lower amplitude of 30μm in the initial stage can ensure the stable dispersion of particles in the liquid and avoid agglomeration caused by excessive stirring. As the reaction proceeds, gradually increasing the amplitude can enhance the force of ultrasound, further promote the contact and reaction between particles and modifiers, and improve the modification efficiency. Ultrasonic time (60-70 minutes): A relatively long time ensures that the modification reaction is fully carried out and that the KH-103 silane coupling agent can effectively adhere to the surface of attapulgite to achieve the ideal modification effect.

[0041] Preferably, in step S3, the semi-frame filter equipment is composed of a filter frame, a filter screen, a clamp and a hydraulic device, and the operating pressure range is: 1-1.5 MPa.

[0042] Semi-frame filter equipment is better able to handle high viscosity liquids because its design allows filtering at higher pressures. This results in better filtration results when processing suspensions containing high viscosity components.

[0043] Preferably, the method for preparing zinc-loaded attapulgite as claimed in claim 1 is characterized in that, in step S3, when stirring at 45-50°C, the stirring speed is 300-500rpm, the stirring time is 2-2.5 hours, and the standing time is 90-100 minutes.

[0044] Compared with the prior art, the present invention has the following beneficial effects: Compared with relying solely on attapulgite to load zinc ions, the present invention solves the problem of low zinc ion loading in attapulgite through modification treatment, and reduces the amount of attapulgite used and reduces costs by increasing the content of zinc ions in attapulgite; through coating operations, accurate delivery of zinc ions is achieved, the bioavailability of zinc ions is improved, the excretion of unabsorbed zinc ions is significantly reduced, the burden on the ecological environment is reduced, and the requirements of sustainable development are met. Compared with the use of zinc oxide, the high-bioavailability zinc-loaded attapulgite prepared by this method can achieve similar or better growth and health performance at a lower zinc dose, providing a cost-saving and efficient zinc supplementation strategy, which has significant advantages when it is necessary to optimize the amount of zinc used, and achieves the purpose of reducing the use and replacing zinc oxide. DETAILED DESCRIPTION

[0045] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0046] A method for preparing zinc-loaded attapulgite with high bioavailability comprises the following steps:

[0047] S1 modification treatment: activating the attapulgite by a two-stage heating method to obtain activated attapulgite; adding the activated attapulgite to ethanol, performing ultrasonic dispersion at 45-50°C, filtering and washing after the ultrasonic dispersion to obtain fine attapulgite; acidifying the fine attapulgite, filtering and washing to obtain modified attapulgite;

[0048] The parameters of attapulgite are as follows: particle size is 20-30nm, length is 1-1.5um; silicon dioxide content is 51.264%-52.139%; magnesium oxide content is 9.765%-9.812%; aluminum oxide content is 12.104%-12.367%; calcium oxide content is 10.375%-10.963%; iron oxide content is 7.379%-7.469%; potassium oxide is 1.864%-1.876%; sodium oxide is 0.689%-0.715%, and the loss on ignition is 6.572-6.749%;

[0049] The specific steps of the activation operation are as follows: the attapulgite is heated at a temperature of 150°C for the first stage. After the first stage of heating is completed, the heating temperature is increased to 280°C for the second stage of heating.

[0050] The parameters of the ultrasonic dispersion operation are as follows: ultrasonic frequency range: 40kHz; ultrasonic power range: 400W; ultrasonic time: 20 minutes; ultrasonic amplitude: 30um; ultrasonic gap: 2mm, ultrasonic device type: immersion ultrasonic generator; the weight ratio of activated attapulgite to ethanol is 1:6.5.

[0051] The specific steps of the acidification treatment operation are as follows: after the fine concave-convex and deionized water are uniformly mixed, a hydrochloric acid solution is added to adjust the pH value to 3.0, and the mixture is stirred at a temperature of 60° C. for 2.5 hours.

[0052] S2 zinc loading: adding modified attapulgite to deionized water, adding biosurfactant, stirring until uniform, obtaining an emulsified suspension, adding zinc sulfate solution to the emulsified suspension, obtaining a mixed suspension, subjecting the mixed suspension to ultrasonic stirring at a temperature of 60-65°C, and during the stirring process, regularly measuring the concentration of zinc sulfate in the mixed suspension to ensure that the concentration of zinc sulfate is not less than 0.1M; after the stirring is completed, filtering and washing are performed to obtain initial zinc-loaded attapulgite;

[0053] According to the weight ratio, the modified attapulgite:biosurfactant is 1:0.003;

[0054] The ultrasonic stirring operation parameters are as follows: ultrasonic frequency: 30kHz, ultrasonic power: 270W; amplitude: starting from 30um and gradually increasing to 50um; ultrasonic time: 65 minutes.

[0055] S3 coating: add carboxylated chitosan to deionized water at 60°C, stir until uniform, then add citric acid to adjust the pH value of the solution to 4-5; then add the initial zinc-loaded attapulgite, continue to stir until uniform, and finally add tannic acid, stir at a temperature of 45, the stirring speed is 300-500rpm, and the stirring time is 2 hours; the standing time is 90-100 minutes, after the stirring is completed, stand for a certain period of time, and finally filter and dry to obtain high bioavailability zinc-loaded attapulgite; in the filtration operation, a semi-frame filtration device is used;

[0056] According to the weight ratio, the weight ratio of carboxylated chitosan: initial zinc-loaded attapulgite: tannic acid is 2.2:100:1.08;

[0057] The semi-frame filter equipment consists of a filter frame, filter screen, clamp and hydraulic device, with an operating pressure range of 1-1.5MPa.

[0058] The highly bioavailable zinc-loaded attapulgite prepared in the specific embodiment focuses on the intestinal health solution for piglets. It can achieve precise release through coating and is not easily processed by gastric juice in the stomach. It releases zinc ions in the intestine. Through the release of zinc ions, it can supplement zinc for the growth and development of piglets. At the same time, the bactericidal ability of zinc ions and the ability of attapulgite to adsorb toxins can inhibit the growth of common pathogenic bacteria such as Escherichia coli, Salmonella and Staphylococcus aureus, thereby reducing diarrhea in piglets, and having the effects of antibacterial and growth promotion.

[0059] The zinc oxide group and the high bioavailability zinc-loaded attapulgite were used to feed the weaned piglets, and the high bioavailability zinc-loaded attapulgite was used as the experimental group for comparison. The results are shown in Table 1:

[0060]

[0061] The results of Table 1 are analyzed as follows: We can compare the difference in zinc usage between the zinc oxide group and the highly bioavailable zinc-loaded attapulgite: Zinc oxide group: The usage was fixed at 2 kg / ton. Highly bioavailable zinc-loaded attapulgite group: Three different usages were tested: 1.0 kg / ton, 1.5 kg / ton and 2.0 kg / ton.

[0062] Comparative analysis of usage: Reduced usage: The usage of high bioavailability zinc-loaded attapulgite at 1.0kg / ton and 1.5kg / ton was significantly lower than that of the zinc oxide group (2kg / ton), but at these lower doses, the additive still showed good effects on terminal body weight and daily weight gain. This shows that compared with traditional zinc oxide, zinc-loaded attapulgite with higher bioavailability can maintain or even improve its effects while reducing usage, reducing the environmental burden caused by excessive zinc.

[0063] Improved effect: Especially at the usage of 1.5kg / ton and 2.0kg / ton, the high-bioavailability zinc-loaded attapulgite group not only had better daily weight gain and feed conversion efficiency than the zinc oxide group while reducing the usage, but also showed a lower diarrhea rate (2.0kg / ton group).

[0064] The content of intestinal mucosal cytokines and immunoglobulins during the use of the product was compared using zinc oxide and high bioavailability zinc-loaded attapulgite, as shown in Table 2.

[0065]

[0066] Table 2

[0067] According to the table of intestinal mucosal cytokine and immunoglobulin content, the zinc oxide group and the high bioavailability zinc-loaded attapulgite group showed similarities in the direction of action: they can effectively reduce the content of certain inflammatory factors (such as TNF-a, IL-1β), increase the level of immunoglobulins such as sIgA, and increase the content of IL-4 and IL-8. The high bioavailability zinc-loaded attapulgite group has the following advantages over the zinc oxide group: Higher sIgA content: In the jejunum, the sIgA content of the high zinc-loaded group was 13.93 mg / mL, while that of the zinc oxide group was 11.65 mg / mL. In the ileum, the high zinc-loaded group was 6.81 mg / mL, while that of the zinc oxide group was 5.76 mg / mL. sIgA is an important component of mucosal immunity, and higher sIgA levels mean stronger local immune defense capabilities. Improved IL-4 levels: In the ileum, the IL-4 content of the high zinc-loaded group was as high as 24.20, which was significantly higher than the 20.27 of the zinc oxide group. IL-4 is an anti-inflammatory cytokine that normally helps regulate immune responses and reduce inflammation.

[0068] Reduction of TNF-a and IL-1β: In the jejunum, the TNF-a (1.79) of the high zinc group was lower than that of the zinc oxide group (1.98). In terms of IL-1β, the high zinc group (3.82) was also lower than that of the zinc oxide group (4.90). In the ileum, although the TNF-a of the high zinc group was similar to that of the zinc oxide group, the high zinc group (4.67) still showed a slight advantage in the IL-1β content. Both TNF-a and IL-1β are pro-inflammatory cytokines, and reducing their levels generally helps to reduce inflammatory responses.

[0069] Better balance: The high-zinc-loaded attapulgite group showed balanced changes in multiple indicators, rather than a significant increase or decrease in a single direction, which suggests that its regulatory effect on the intestinal environment is more stable and holistic.

[0070] Overall, the high-bioavailability zinc-loaded attapulgite group showed certain advantages in increasing the level of immunoglobulins (especially sIgA) and regulating the content of key inflammatory factors (such as IL-4, TNF-a and IL-1β), indicating that it is more effective in protecting intestinal health and enhancing immune function.

[0071] High bioavailability zinc-loaded attapulgite has a significant inhibitory effect on Escherichia coli, Salmonella and Staphylococcus aureus. The specific experimental steps are as follows:

[0072] 1. Experimental design: Sample preparation: After the high bioavailability zinc-loaded attapulgite is shelled, it is the initial zinc-loaded attapulgite in the specific embodiment, and then 0.1% initial zinc-loaded attapulgite liquid is prepared as the test group.

[0073] Select bacterial strains: Escherichia coli, Salmonella, Staphylococcus aureus,

[0074] 2. Experimental steps: Inoculation: The three bacteria mentioned above were inoculated on nutrient agar plates respectively, and the test group and treatment were used; Culture: The inoculated culture dish was placed in a 37°C incubator for 24 hours. Counting: The incubated plate was used to count the colonies and calculate the colony forming unit (CFU). After multiple experiments, the experimental data are shown in Table 3:

[0075]

[0076]

[0077] Table 3

[0078] The above experimental data prove that 0.1% initial zinc-loaded attapulgite has a significant inhibitory effect on Escherichia coli, Salmonella and Staphylococcus aureus, and the inhibition rate reaches more than 95%.

[0079] The specific embodiments described herein are merely examples of the spirit of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but will not deviate from the spirit of the present invention or exceed the defined scope. Although the present invention is described and described in detail in the foregoing description, such description and description are considered to be illustrative or exemplary rather than restrictive. It should be understood that within the scope of the following claims, changes and modifications may be made by a person of ordinary skill in the art.

Claims

1. A method for preparing zinc-loaded attapulgite with high bioavailability, characterized in that: The preparation method of zinc-loaded attapulgite with high bioavailability comprises the following steps: S1 modification treatment: activating the attapulgite by a two-stage heating method to obtain activated attapulgite; adding the activated attapulgite to ethanol, performing ultrasonic dispersion at 45-50°C, filtering and washing after the ultrasonic dispersion to obtain fine attapulgite; acidifying the fine attapulgite, filtering and washing to obtain modified attapulgite; S2 zinc loading: adding modified attapulgite to deionized water, adding biosurfactant, stirring until uniform, obtaining an emulsified suspension, adding zinc sulfate solution to the emulsified suspension, obtaining a mixed suspension, subjecting the mixed suspension to ultrasonic stirring at a temperature of 60-65°C, and during the stirring process, regularly measuring the concentration of zinc sulfate in the mixed suspension to ensure that the concentration of zinc sulfate is not less than 0.1M; after the stirring is completed, filtering and washing are performed to obtain initial zinc-loaded attapulgite; According to the weight ratio, the modified attapulgite:biosurfactant is 1:0.0025-0.003; S3 coating: add carboxylated chitosan to deionized water at 40-60°C, stir until uniform, then add citric acid to adjust the pH value of the solution to 4-5; then add the initial zinc-loaded attapulgite, continue to stir until uniform, and finally add tannic acid, stir at a temperature of 45-50°C. After stirring, let it stand for a certain period of time, and finally filter and dry to obtain zinc-loaded attapulgite with high bioavailability; in the filtration operation, a semi-frame filtration equipment is used.

2. The method for preparing zinc-loaded attapulgite with high bioavailability according to claim 1, characterized in that: In step S1, the specific steps of the activation operation are as follows: the attapulgite is heated at a temperature of 100-200°C for the first stage, and after the first stage heating is completed, the heating temperature is increased to 250-280°C for the second stage heating.

3. The method for preparing zinc-loaded attapulgite with high bioavailability according to claim 1, characterized in that: In step S1, the parameters of attapulgite are as follows: particle size is 20-30nm, length is 1-1.5um; silicon dioxide content is 51.264%-52.139%; magnesium oxide content is 9.765%-9.812%; aluminum oxide content is 12.104%-12.367%; calcium oxide content is 10.375%-10.963%; iron oxide content is 7.379%-7.469%; potassium oxide is 1.864%-1.876%; sodium oxide is 0.689%-0.715%, and loss on ignition is 6.572-6.749%.

4. The method for preparing zinc-loaded attapulgite with high bioavailability according to claim 1, characterized in that: In step S1, the parameters of the ultrasonic dispersion operation are as follows: ultrasonic frequency range: 30kHz to 50kHz; ultrasonic power range: 300W to 500W; ultrasonic time range: 15 minutes to 25 minutes; ultrasonic amplitude: 20-40um; ultrasonic gap: 1-3mm, ultrasonic device type: immersion ultrasonic generator; the weight ratio of activated attapulgite to ethanol is 1:5.38-7.

17.

5. The method for preparing the highly bioavailable zinc-loaded attapulgite according to claim 1, characterized in that: In step S1, the specific steps of the acidification treatment operation are as follows: after the fine attapulgite and deionized water are uniformly mixed, a hydrochloric acid solution is added to adjust the pH value to 3.0-3.3, and the mixture is stirred at a temperature of 60° C. for 2-2.5 hours.

6. The method for preparing zinc-loaded attapulgite with high bioavailability according to claim 1, characterized in that: In step S2, the ultrasonic stirring operation parameters are as follows: ultrasonic frequency: 28-30kHz; ultrasonic power: 250-270W; amplitude: starting from 30um and gradually increasing to 50um; ultrasonic time: 60-70 minutes.

7. The method for preparing zinc-loaded attapulgite with high bioavailability according to claim 1, characterized in that: In step S3, according to the weight ratio, the weight ratio of carboxylated chitosan: initial zinc-loaded attapulgite: tannic acid is 2.2-2.4:100:1.08-1.

1.

8. The method for preparing zinc-loaded attapulgite with high bioavailability according to claim 1, characterized in that: In step S3, the semi-frame filtering equipment is composed of a filter frame, a filter screen, a clamp and a hydraulic device, and the operating pressure range is: 1-1.5MPa; when stirring at 45-50°C, the stirring speed is 300-500rpm, the stirring time is 2-2.5 hours; and the standing time is 90-100 minutes.

Citation Information

Patent Citations

  • A kind of attapulgite surfactant and its preparation and application

    CN117256728B